(untitled) (SAARC Journal of Agriculture, 2023)
Sweet pepper is one of the most important vegetable crops and its demand is increasing day by day in Bangladesh indicating need for varietal improvement program. Eleven sweet pepper genotypes from native and exotic sources were characterized for twenty-five morphological traits using vegetative and reproductive appearances at Bangladesh Institute of Nuclear Agriculture, Mymensingh, from November 2021 to March 2022. Noticeable variation was observed among twenty-five qualitative traits (25) studied. Nineteen (19) traits showed undisputable variation. Higher number (9 genotypes) of light purple, purple and dark purple color at node indicated high amount of anthocyanin content. Leaf shape is used as genotypes identifier at vegetative stage and three types of leaves were found with dark green color (6 genotypes) that is highly correlates with yield. In case of flower, 100% white color corolla indicates higher number of fruit set. Entire genotypes exhibited one or more exclusive characters especially fruit shape and color which could be used as important breeding materials. CKN-1 and CKN-8 had the highest yield per plant (367.6 and 362.04 grams, respectively), making them potentially good for cultivation, whereas plant height, fruit number, weight, length, and diameter varied among the selected genotypes. A positive Correlation was observed among the traits and genetic distance value ranged from 0.17 to 0.68 among the selected genotypes. However, selection of genotypes with desirable morphological characteristics can be used for their exploitation of future research program. SAARC J. Agric., 21(1): 13-24 (2023)